Influence of two garlic-derived compounds, propyl propane thiosulfonate (PTS) and propyl propane thiosulfinate (PTSO), on growth and mycotoxin production by Fusarium species in vitro and in stored cereals - Mylona, Kalliopi; García-Cela, Esther; Sulyok, Michael; Medina, Angel; Magan, Naresh (MDPI, 2019)
Two garlic-derived compounds, Propyl Propane Thiosulfonate (PTS) and Propyl Propane Thiosulfinate (PTSO), were examined for their efficacy against mycotoxigenic Fusarium species (F. graminearum, F. langsethiae, F. verticillioides). The objectives were to assess the inhibitory effect of these compounds on growth and mycotoxin production in vitro, and in situ in artificially inoculated wheat, oats and maize with one isolate of each respectively, at different water activity (aw) conditions when stored for up to 20 days at 25 °C. In vitro, 200 ppm of either PTS or PTSO reduced fungal growth by 50–100% and mycotoxin production by >90% depending on species, mycotoxin and aw conditions on milled wheat, oats and maize respectively. PTS was generally more effective than PTSO. Deoxynivalenol (DON) and zearalenone (ZEN) were decreased by 50% with 80 ppm PTSO. One-hundred ppm of PTS reduced DON and ZEN production in wheat stored at 0.93 aw for 20 days, although contamination was still above the legislative limits. Contrasting effects on T-2/HT-2 toxin contamination of oats was found depending on aw, with PTS stimulating production under marginal conditions (0.93 aw), but at 0.95 aw effective control was achieved with 100 ppm. Treatment of stored maize inoculated with F. verticilliodies resulted in a stimulation of total fumonsins in most treatments. The potential use of such compounds for mycotoxin control in stored commodities is discussed.
Keywords: Fusarium; mycotoxins; garlic-derived extracts; green chemistry; abiotic factors; fungi; wheat; maize; oats